Agricultural Productivity and Poverty in Rural Sudan - Ali, Haseeb (World Bank, Washington, DC, 2021)
The remainder of this paper is organized as follows. Section two describes the state of the rural population in Sudan, by first discussing the spatial distribution of poverty across the states as well as changes in poverty levels between 2009 and 2014-15. It also describes the profile of poor rural households using characteristics such as their incomes, consumption, and assets. Section three focuses on the practice of agriculture in Sudan. It documents the agriculture-specific characteristics of households, such as choice of crops, use of inputs, irrigation, plot size, and credit access. We use these characteristics to illustrate the profile of rural farmers in Sudan and identify differences between poor and non-poor farmers. Section four describes agricultural yields across Sudan and relates these measures of farm productivity to the previously described farm characteristics to identify constraints to agricultural productivity. Section five concludes with a summary of the main findings and policy recommendations.